Teacher’s experiences in working with children with developmental disabilities - Matić, Ivana; Škrbić, Renata; Kerkez, Jelena; Simić, Ljiljana; Jankelin, Isidora (Norma, 2023)
Teachers are often mentioned among the key factors of the quality of the teaching process, and it is considered that teachers with experience in working with children with disabilities are more confident in their professional knowledge and skills and have high expectations of their students, despite the fact that some of them may have severe degree of developmental disability. The successful implementation of inclusive education in the sense of placing students with disabilities in classrooms within the regular system of education could contribute to the competence of teachers in this area, but also to their motivation to provide appropriate instructions and assistance. The goal of the research is to determine what type of developmental disabilities teachers most often encountered within the framework of direct work in education. The sample consisted of 288 teachers, and a questionnaire created for the purposes of this research was used. Based on the results of the research, it was determined the presence of differences in the type of disabilities among students included in the regular education system, compared to schools for the education of children with developmental disabilities, as well as a greater presence of children with developmental disabilities in the older grades of elementary school. There are also differences in the experience of teachers employed in urban areas compared to those employed in rural areas.
Keywords: inclusive education; children with developmental disabilities; teachers